Subtype-specific survival and regeneration of retinal ganglion cells in response to injury - Mary L. Tapia; Gabriel Nascimento-dos-Santos; Kevin K. Park (Frontiers in Cell and Developmental Biology, 2022)
Retinal ganglion cells (RGCs) are a heterogeneous population of neurons that function synchronously to convey visual information through the optic nerve to retinorecipient target areas in the brain. Injury or disease to the optic nerve results in RGC degeneration and loss of visual function, as few RGCs survive, and even fewer can be provoked to regenerate their axons. Despite causative insults being broadly shared, regeneration studies demonstrate that RGC types exhibit differential resilience to injury and undergo selective survival and regeneration of their axons. While most early studies have identified these RGC types based their morphological and physiological characteristics, recent advances in transgenic and gene sequencing technologies have further enabled type identification based on unique molecular features. In this review, we provide an overview of the well characterized RGC types and identify those shown to preferentially survive and regenerate in various regeneration models. Furthermore, we discuss cellular characteristics of both the resilient and susceptible RGC types including the combinatorial expression of different molecular markers that identify these specific populations. Lastly, we discuss potential molecular mechanisms and genes found to be selectively expressed by specific types that may contribute to their reparative capacity. Together, we describe the studies that lay the important groundwork for identifying factors that promote neural regeneration and help advance the development of targeted therapy for the treatment of RGC degeneration as well as neurodegenerative diseases in general.